Innovative Educational Technology: The Impact of an Interactive Video Game on History Teaching for Basic Education Students and its Link to Cultural Identity in Migration Contexts - Aguayza-Mendieta, Carlos (2023)
This article presents a study on how the creation of a video game to teach history in basic education students strengthens learning and serves as an interactive edu-cational resource for teachers, transforming the traditional approach to teaching. This generates a greater interest of students in learning, considering the im-portance of maintaining links with their culture of origin in the formation of their identity when facing migration. The study was divided into three phases: an ex-ploratory investigation in the Pablo Arturo Suarez educational unit, the develop-ment of the video game using an agile methodology with an adaptive algorithm that modifies the content according to the player's progress, and finally, the evalu-ation of a specific group of students. The results demonstrated a 27.78% increase in students' knowledge compared to the conventional method of learning.